Emotions, sanctions and cooperation - Mateus Joffily; David Masclet; Charles N. Noussair; Marie Claire Villeval (Institute for the Study of Labor (IZA), 2011)
We use skin conductance responses and self-reports of hedonic valence to study the emotional basis of cooperation and punishment in a social dilemma. Emotional reaction to free-riding incites individuals to apply sanctions when they are available. The application of sanctions activates a virtuous emotional circle that accompanies cooperation. Emotionally aroused cooperators relieve negative emotions when they punish free riders. In response, the free-riders experience negative emotions when punished, and increase their subsequent level of cooperation. The outcome is an increased level of contribution that becomes the new standard or norm. For a given contribution level, individuals attain higher levels of satisfaction when sanctioning institutions are in place.
urn:nbn:de:101:1-201104134145
Keywords: C92; D62; D63; D64; D74; 330; emotions; sanctions; cooperation; experiment; skin conductance responses; Gefangenendilemma; Trittbrettfahrerverhalten; Strafe; Emotion; Kooperation; Test